A Comprehensive Workflow for High Resolution 3D Solar Photovoltaic Potential Mapping in Dense Urban Environment: A Case Study on Campus of Delft University of Technology. Issue 5 (10th May 2022) - Zhou, Yilong; Verkou, Maarten; Zeman, Miro; Ziar, Hesan; Isabella, Olindo
Abstract : Solar Photovoltaic Potential In article number 2100478, Hesan Ziar and co‐workers developed a semi‐automatized workflow to estimate residential solar photovoltaic (PV) potential, which only requires LiDAR data and building footprints as inputs, and delivers accurate geo‐referenced 3D building models, annual solar irradiation map, annual DC/AC yield maps, and prioritizes roof segments based on their PV potential.